THERAPEUTIC EQUIVALENCE OF ORIGINAL CLOPIDOGREL (PLAVIX) AND ITS GENERIC (EGITROMB). RESULTS OF COMPARATIVE RANDOMIZED CROSS-OVER BLIND STUDY - V. V. Yakusevich; A. S. Petrochenko; V. A. Simonov; N. Yu. Levshin; A. D. Deev (Столичная издательская компания, 2016)
Aim. To study therapeutic equivalence (efficacy, safety and tolerability) of original clopidogrel (Plavix) and its generic (Egitromb) in patients of high cardiovascular risk. Material and methods. Thirty one patients with coronary heart disease and indications for clopidogrel therapy were involved into the randomized cross-over blind study. Half of the patients received original clopidogrel (75 mg daily) during the first 2 weeks and then they received generic clopidogrel in the same dose during next 2 weeks. Another half of the patients received the drugs in reverse order. Antiplatelet activity of Plavix and Egitromb was estimated by effects on ADP-induced platelet aggregation initially and after 2 weeks of treatment with each drug. Study blinding was provided by the following approach: doctors of cardiology clinic performed clinical monitoring and drug distribution; coded blood samples for platelet aggregation assessment were studied in independent laboratory of thrombosis; statistical data analysis was performed by biostatistics expert in other research center. Results. 2-week therapy with each drug led to a significant decrease of ADP-induced platelet aggregation which remained low after switching from original drug to generic and vice versa. Aggregation dynamics did not depend on the first administered drug. There were no significant differences between aggregation changes as a result of treatment with original or generic drug. No one adverse event was observed in association with both drugs therapy. Conclusion. Generic drug Egitromb (Egis, Hungary) and original clopidogrel Plavix (Sanofi-Aventis, France) have equivalent antiplatelet effect.